﻿HPLC-DAD analysis of flavonoids and hydroxycinnamic acids in Aster novi-belgii L. - Diana Demydiak; Liudmyla Slobodianiuk; Oleg Gerush; Liliia Budniak; Valeriia Sydor; Olha Skrynchuk; Olha Demydiak; Nadiia Panasenko; Vadym Ratynskyi (Pensoft Publishers, 2023)
Aster novi-belgii is a perennial ornamental herb native to eastern Canada and the United States of America, cultivated in Ukraine. This species should be considered a possible source of phenolic compounds, principally hydroxycinnamic acids and flavonoids. Therefore, in this study, the aim was to determine these compounds in Aster novi-belgii by HPLC-DAD analysis, and validation of this chromatographic method and lay a scientific and technical basis for the utilization and development of the plant resources of the cultivated plants of the genus Aster. The HPLC-DAD method determined the flavonoids and hydroxycinnamic acids composition and content in the herb of Aster novi-belgii L. The HPLC-DAD method allowed the detection of 13 phenolic compounds, namely 6 hydroxycinnamic acids (chlorogenic, sinapic, caffeic, syringic, trans-cinnamic, trans-ferulic acids), and 7 flavonoids (kaempferol 3-O-beta-D-glucoside, naringin, quercetin, luteolin, rutin, kaempferol, rhamnetin). The quantitative detection showed that the main hydroxycinnamic acids were chlorogenic acids (15069.21 ± 0.34 µg/g) and sinapic acids (949.95 ±0.22 µg/g). Concerning flavonoids, the largest amounts were kaempferol 3-O-beta-D-glucoside (8989.79 ±0.31 µg/g) and naringin (2092.02 ± 0.26 µg/g). HPLC-DAD method was evaluated in terms of linearity, precision, accuracy, limits of quantification, and limits of detection. The calibration curves of reference substances were linear (R2 ≥ 0.997), the LODs were in the range of 0.21-1.71 µg/mL, and the LOQs - of 0.48-5.19 µg/mL, respectively. Our phytochemical research confirms that the study material is a rich source of hydroxycinnamic acids and flavonoids. Findings mean that Aster novi-belgii is a promising plant because of the important role of these phenolic compounds in many biological processes.